Connection between Personal Values and Music Preferences - Kurapov, Anton; Kandykin, Mykhailo (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
This article describes the main correlations that were obtained between music preferences and personal values. It has been discovered that personal values play a significant role in people’s music preferences and they are at the forefront in proposing a map that links personal values to music preferences. According to the results, music preferences can be defined by personal values since people tend to listen to a specific type of music if corresponding values are projected such as conservatism and openness. In this case, music is broken into four preference dimensions which include reflective and complex for folk, jazz, and classical, rebellious and intense comprising of punk, rock, and alternate, conventional and upbeat comprising of pop, country, and soundtracks, and lastly rhythmic and energetic including funk, electronica, hip-hop, and soul. Besides, preferences may be defined by socio-demographic characteristics such as age and gender such that the young people tend to prefer music because of what the other peers listen to and enjoy music in social places such as bars, restaurants, and music festivals, middle-aged people listen to the music of their preferences and at the time of their choosing at homes or while carrying out activities, the aged tend to have less music preference but some cannot do anything without listening to music and therefore have to keep their preference music always. Males tend to focus on certain genres of music such as heavy metal and rock which are associated with cognitive listening and demonstrates a negatively conservative nature of music while females prefer listening to pop music more than males. This article discloses the main results that were obtained in the empirical study of different articles concerning the topic of the relationship between personal values and music preferences. No such research was conducted on Ukrainian-speaking samples before.